RESPONSE TO NEW S. 1440 COMPROMISE (Tufts Archival Research Center, 2007)
Talking points in response to the new S. 1440 compromise on smoking legislation. Argues government smoking regulation is unnecessary and that collective bargaining will be sacrificed. Questions evidence showing that environmental tobacco smoke is harmful.